Makna Simbol-Simbol Dalam Tradisi Mbeleh Golekan Di Desa Kandangan, Kabupaten Kediri - Fisabilillah, Aqillah; Adelya Dewi; Tri Naryawant, Eric Rayfaido o; Septianingrum, Eka Lutviana; Sugiantoro, Sugiantoro; Setyawan, Katon Galih (Program Studi Pendidikan Sejarah - Universitas Samudra, 2024)
The country is known for its various traditions and rituals that have deep values in the lives of its people. Mbeleh golekan is a ritual practice rich in meaning and symbols, involving the slaughter of dolls as a tribute to ancestors as well as the use of elements such as brown sugar, seven-figure flowers, cows, and ingkung, each of which reflects gratitude, salvation, and cultural identity. The data collection techniques in this study used qualitative methods with an ethnographic approach, literature studies, and interviews to explore the meanings and experiences of the informants related to mbeleh golekan. The literature study involved collecting data from journals that discuss local culture, customary rituals, and traditions of communities in Indonesia, especially in the context of East Java. Data from the interviews were then compared with the literature review to ensure the validity and consistency of the findings. Through a structural theory approach, this article analyses how the symbols interact and create a network of meanings that strengthen social relations within the community. By maintaining the mbeleh golekan tradition, the community not only preserves cultural heritage, but also strengthens solidarity and understanding of the values passed down from generation to generation. This research is expected to provide insight into the importance of maintaining cultural diversity and the meanings behind traditional practices in the context of modern society.